Knowledge, Inspection and the Work of Governing - Ozga, Jenny (2014)
This paper discusses the relationship between knowledge and governing as exemplified by the governing work of school inspection. We argue that there have been changes in the practices and processes of both governance and knowledge in recent years, and suggest that these changes are interdependent, contributing to a new relationship between governing and knowledge. The interdependence of governing and knowledge may be identified through attention to the ways in which expertise, especially expertise in developing ‘practical knowledge’ has moved from the traditional task of policy-informing conventionally carried out through elite or professional knowledge production in bureaucratic, hierarchical relations, to the ‘applied’ or integrated use of expertise in the formation of policy in a more complex, networked form of governing. The paper discusses approaches to conceptualising these transformations of governance and of knowledge, before offering some exemplification of the governing-knowledge relationship and its working in practice that draws primarily on data on inspection in England, but with some contrasting points from Scotland. For more detailed discussion of the knowledge-governing relationship and its impact on inspection in Sweden see Lindgren 2014 (in this issue).